Օտարականի կերպարը Հակոբ Կարապենցի պատմվածքներում - Գոհար Սահակյան (ՀՀ ԳԱԱ հրատ.)
The hero of many stories of Karapents is a lonely stranger, a refugee Armenian, Russian or Greeks who have appeared in the United States, and as a place of action, he chooses a place where people meet in a short period of time, but then they are forced to divorce, even without managing recognize each other to the end, just recording, even being a stranger, some kind of affection unites them, and it’s the fate that makes everyone be a friendly wayfarer stranger. Герой многих рассказов Карапенца - одинокий незнакомец, эмигрант армянин, русский или грек, который оказался в Соединенных Штатах. Как место действий для своих рассказов он выбирает такую среду, где люди встречаются за короткий промежуток, но затем вынуждены расставаться, не успевая узнавать друг друга до конца, фиксируя лишь то, что несмотря на то, что они не знакомы и чужды, их объединяет какая-то родственность, и это судьба, которая делает всех родственными прохожими незнакомцами.
Keywords: Գրականություն